Sonoleaching development of a rapid determination of Pb from stabilized waste using ultrasound assisted leaching - Bellotindos, Luzvisminda Malli (2009)
This study develops an ultrasonic assisted leaching procedure, known as sonoleaching process for a fast determination of Pb form stabilized waste that could improve the Toxicity Characteristic Leaching Procedure (TCLP) of the United States Environmental Protection Agency (USEPA). The TCLP is a regulatory procedure which requires eighteen (18) hours of extraction for the determination of hazardous wastes/contaminants as to its toxicity charateristic. The results show that it improves this regulatory procedure by shortening the extraction time by 97.2%, decreasing the weight of waste to be used in the analysis by 95% and decreasing the volume of the extraction fluid used by 95%. The significant improvement in the TCLP is due to the application of ultrasound irradiation. Lead (Pb) is the major heavy metal selected in this study.
The optimal ultrasonic conditions that give comparable recovery with TCLP are as follows: a sonication time of 30 minutes and initial bath temperature of 30 ˚C.
The leaching of lead (Pb) from synthetic soil using the sonoleaching process follows a second order kinetics with an initial dissolution rate (r) of -0.006, and rate constant k of -0.0217; whereas, the leaching of lead in the presence of Cu in synthetic soil using the sonoleaching process follows a second order kinetics with initial dissolution rate (r) = -0.004, rate constant (k) = -0.025 for Pb and r= -0.008, k= -0.01215 for Cu. The sonoleaching of slag and stabilized slag also follow a second order kinetics with initial dissolution rate (r) =0.1581, and rate constant (k) = 0.00636 and initial dissolution rate (r) = -0.0513 and rate constant (k) = -0.0125 respectively.
The sonoleaching of lead (Pb) from a synthetic soil and stabilized slag exhibit a second order dissolution process. The data fit a linearized form of the second order dissolution equation which resulted in a straight line. Extraction with the use of ultrasound is a physical change rather than a chemical change. Ultrasound hastened the dissolution due to increase in surface area, turbulence, transport, and temperature.
The results show that an ultrasonic assisted procedure is a potential treatment that gives a comparable results for TCLP. This paves way for a modified TCLP with the following advantages : 1) the cost for the heavy metals determination will be greatly reduced as less energy will be consumed in a much reduced extraction time; 20 a short time is needed to determine the metals content; and 3) the amount of liquid wastecontaining pollutants which will eventually be disposed to the environment will be minimized.
Thesis (Ph.D. in Chemical Engineering)--University of the Philippines Diliman.
Keywords: Soils -- Leaching; Lead; Leaching